2023
DOI: 10.1021/acssuschemeng.2c07575
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Electronic Structure of α-Fe2O3 by Doping Atomically Dispersed Ce for the Transfer Hydrogenation of Nitroaromatics Using Stoichiometric Hydrazine Hydrate

Abstract: The metal-oxide-catalyzed transfer hydrogenation of nitroarenes to anilines by hydrazine hydrate has been widely reported; however, the risk of explosion resulting from excess hydrazine hydrate and high temperatures and complex preparations of these catalysts immensely hinder their industrial application. Herein, we use a simple co-precipitation method to synthesize atomically dispersed Ce-doped α-Fe 2 O 3 (Ce 0.025 -Fe 2 O 3 -350 °C), which can completely reduce nitroarenes using stoichiometric hydrazine hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…The v/u, v′′/u′′ and v′′′/u′′′ peaks can be attributed to Ce 4+ , while the v 0 /u 0 and v′/u′ peaks are related to Ce 3+ . 54–56 It was found that there are abundant Ce 3+ species existed in the Pd–Ce/SiO 2 /Ni foam reactor, which is well explained by the electron transfer effect between Pd and Ce. The partial reduction of Ce 4+ during the catalyst reduction process may also contribute to the generation of Ce 3+ .…”
Section: Resultsmentioning
confidence: 96%
“…The v/u, v′′/u′′ and v′′′/u′′′ peaks can be attributed to Ce 4+ , while the v 0 /u 0 and v′/u′ peaks are related to Ce 3+ . 54–56 It was found that there are abundant Ce 3+ species existed in the Pd–Ce/SiO 2 /Ni foam reactor, which is well explained by the electron transfer effect between Pd and Ce. The partial reduction of Ce 4+ during the catalyst reduction process may also contribute to the generation of Ce 3+ .…”
Section: Resultsmentioning
confidence: 96%
“…The decomposition of N 2 H 4 ·H 2 O results in the formation of N 2 and H 2 and some studies revealed that partial decomposition also occurs to produce NH 3 and N 2 when N 2 H 4 ·H 2 O is used in excess amount. Due to the redox nature of metal species, N 2 H 4 ·H 2 O produces in situ hydrogen protons and metal hydrides, which play a crucial role in transfer hydrogenation reactions. normalN 2 normalH 4 normalN 2 + 2H 2 3N 2 normalH 4 normalN 2 + 4NH 3 …”
Section: Various Hydrogen Sources For Cth Reactionsmentioning
confidence: 99%
“…A heterogeneous catalyst plays an important role in many established and emerging chemical processes, where high performance requires rational design using various synthesized strategies, tuning the geometric structure and microenvironment of active sites, such as coordination status and electronic properties 1–6 Therein, micro- and nanometer-sized materials with hollow interiors as catalysts have attracted particular attention, which demonstrate obvious advantages, such as effectively isolating catalytic species, improving mass transfer, and enhancing the selectivity by controlling pore sizes in the shells. This specific structure can help to achieve excellent performance in chemical synthesis, electrocatalysis, photocatalysis, energy storage and conversion, and other applications.…”
Section: Introductionmentioning
confidence: 99%